Virtual network resource management for next-generation networks. - Leon-Garcia, A. (IEEE Communications magazine)
The multilayer structure of transport networks presents a key challenge in network resource management. In this article we present a virtual network approach to the management of transport network resources. We describe the approach as developed for the management of large-scale ATM networks and discuss the application to the next generation of multilayer transport networks.